2008
DOI: 10.1080/03079450802043783
|View full text |Cite
|
Sign up to set email alerts
|

Rapid selection in chickens of subpopulations within ArkDPI-derived infectious bronchitis virus vaccines

Abstract: We examined spike (S) gene sequences of the virus populations of four different commercial ArkDPI-derived infectious bronchitis coronavirus vaccines before and during a single passage in specific pathogen free chickens. We found different degrees of genetic heterogeneity among the four vaccines before passage in chickens, ranging from no apparent heterogeneity to heterogeneity in 20 positions in the S gene. In all except one position, nucleotide differences were non-synonymous. The majority of amino acid diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…This substitution was maintained for P70 and P110, indicating that this residue was likely to be important for virus pathogenicity. However, other amino acid substitutions in the S1 protein were not observed between the M41 vaccine strain and M41 challenge strain [50], the 4/91 pathogenic and 4/91 attenuated strains [9,51], the TW1171/92 pathogenic and TW1171/92 attenuated strains, the TW2296/95 pathogenic and TW2296/95 attenuated strains, the TW2575/98 pathogenic or TW2575/98 attenuated strains [48], or the ArkDPI strain [52]. Investigations with other coronaviruses have shown that the S protein is a determinant of pathogenicity; however, the replacement of the S protein gene of the apathogenic Beaudette strain with that of the pathogenic M41 strain resulted in a recombinant virus that was still not pathogenic [53].…”
Section: Discussionmentioning
confidence: 91%
“…This substitution was maintained for P70 and P110, indicating that this residue was likely to be important for virus pathogenicity. However, other amino acid substitutions in the S1 protein were not observed between the M41 vaccine strain and M41 challenge strain [50], the 4/91 pathogenic and 4/91 attenuated strains [9,51], the TW1171/92 pathogenic and TW1171/92 attenuated strains, the TW2296/95 pathogenic and TW2296/95 attenuated strains, the TW2575/98 pathogenic or TW2575/98 attenuated strains [48], or the ArkDPI strain [52]. Investigations with other coronaviruses have shown that the S protein is a determinant of pathogenicity; however, the replacement of the S protein gene of the apathogenic Beaudette strain with that of the pathogenic M41 strain resulted in a recombinant virus that was still not pathogenic [53].…”
Section: Discussionmentioning
confidence: 91%
“…Consequently following combined vaccination, the efficiently replicating Mass vaccine adds difficulty to the establishment of the Ark vaccine population. Furthermore, in the previous study reported by van Santen and Toro (2008) no selection of Mass vaccine virus subpopulations was observed; the S1 sequence of virus detected in vaccinated chickens was identical to that of the predominant S1 sequence found in vaccine vials. This may mean the vast majority of viruses contained in the Mass vaccine are able to efficiently replicate in the chicken, unlike Ark vaccine where only a minor component is able to efficiently replicate.…”
Section: Discussionmentioning
confidence: 51%
“…Previously reported studies have shown that Arkansas type vaccine is the most prevalent virus in the commercial broilers and is capable of persisting in the flock (Jackwood et al, 2005;McKinley et al, 2008;Nix et al, 2000;van Santen and Toro, 2008). Vaccine virus was used in this experiment because colony houses (necessary to house the number of birds needed for the experiment) are not biologically secure, preventing us from using pathogenic isolates of IBV.…”
Section: Discussionmentioning
confidence: 99%